Open Innovation Strategy in Indonesia ICT Industries - Yuana, Rivira; Prasetio, Eko Agus; Syarief, Rizal; Arkeman, Yandra; Suroso, Arif Imam (Universitas Prasetiya Mulya, 2022)
The research objective is establishing the relationship between business model, open innovation, and a firm’s performance in context-based corporate accelerator program held by Indonesia ICT industries. The crucial relationships between startup and industry collaboration are: co-creation; IP-sharing; reducing R&D costs; the need for risk sharing; and the primary driver of companies’ sustainability growth. Co-creation becomes the most reliable driver in the issue of the importance of collaboration, and it leads to an independent factor that should be firstly developed and continuously improved. The IP-sharing and risk-sharing factors are both reliable drivers but medium dependent. The startups and industries must have a proper contractual agreement once they decide to share the IP and risk. The integrity factor will be necessary for mutual benefit. Reducing R&D costs and the main driver of the company’s sustainability growth are the dependent variables or outcomes of the collaboration between startups and leading industries.